Potency of commercial TiO2‐P25 nanoparticles to form stainless steel protective coating. Issue 3 (11th February 2017) - Pourmoalem, Mansour; Naghibi, Sanaz
Abstract: This research reports for the first time the surface coating of steel samples with commercial nanoparticles of TiO2 . Aiming to improve the substrate corrosion behavior, a stable suspension containing TiO2 ‐P25 nanoparticles and polyvinyl alcohol in the water was prepared and the coating was applied on the surface of the substrate via dip‐coating. Heat treatment led to the formation of strong connection between the substrate and the coating film. Scanning electron microscopy and scanning probe microscopy were utilized to scrutinize the samples in terms of topography and microstructure. In addition, the samples corrosion behavior was investigated through Tafel polarization and impedance spectroscopy. The results showed that one‐step of sample dip‐coating in sol or heat treatment at 600°C cannot provide for desirable and appropriate physical circumstances in the thin film. The applied thin film showed the highest corrosion behavior improvement when the sample was coated with two or three films and the heat treatment was carried out at 400°C. In this respect, according to the Tafel curves, the applied coating efficiency was measured to be approximately 90%. The electrochemical impedance spectroscopy results indicated that the reference sample was single‐time constant and the coated sample was double‐time constant. Applying the coating increased impedance, reduced the capacitive element, and diminished the resistance area. All three mentioned factors contributed to the enhancement of corrosion behavior.